Byzantine Icons and Other Sacred Images in the Travel Notes of Grigorovich-Barskiy - Buzykina, Yulia N. (Actual Problems of Theory and History of Art, 2022)
The article analyses the descriptions of Christian religious images from the itineraries of Vassiliy Grigorovich-Barskiy. Among the descriptions chosen by the author, there are Catholic ones, such as the Plague Pillar and Our Lady of Loreto, as well as Byzantine Orthodox ones, which have specific features, such as non-availability for the eyes, worshipping with a stone, and relief sculpture as an art form. The research revealed that the critical position of Barskiy is activated when contemplating Orthodox icons with some unusual features, while the unusual (Plague Pillar) and inaccessible (Our Lady of Kykkos, Saidanaya) objects do not cause him to question their competence, Orthodoxy, and, in general, their presence behind icon cases and covers. In his critics, Barskiy uses tools from rhetorics and philosophy, which he studied at the Kiev-Mohyla Academy. He criticizes only what is more or less familiar to him, which means that he is able to comprehend and apply the skill. Unusual objects are rewarded with a neutral-benevolent description. Thanks to Mikhail Abramov Foundation, Moscow.